Wear Studies of Al2O3-ZrO2∙5CaO Composite Coatings for Tribological Applications - ., Abhinav; Krishnamurthy, N; Jain, Ranjana (International Journal of Engineering and Technology, 2018)
A composite mixture of Metco 105 SFP, 99.9% Al2O3 and Metco 201 NS, ZrO2.5CaO were blended in the pursuit of high hardness and improved wear resistance characteristics for tribological applications. In this context a composite mixture of alumina and calcia stabilized zirconia in 50:50 by wt. % proportion was developed, and applied over Al-6061 substrates. Atmospheric plasma spray coating technique was used to develop the coating systems. The ASTM G132 standard, a pin-on-disk tribometer was used to determine the specific wear rate at different normal loads of 5 N, 10 N and 15 N. Experimental results revealed that the top coat primarily subjected to sliding and localized abrasion and also confirmed with SEM micrograph. Sliding has mainly occurs in the plane of <111>, <200>, <220>, <311>, <222> found in the XRD analysis. Irrespective of the applied normal loads the coefficient of friction doesn’t influences much in the abrasive wear studies. However, wear mechanism was found to primarily dependent on the phases and on the crystallographic structure of the material used.